Contemporary economic problems 1978 - Fellner, William (Washington : American Enterprise Institute for Public Policy Research, 1978)
This volume deals with the current controversy on anti-inflation policy. Because it is convenient to identify this focal point in macroeconomic terms, the introduction supplement's Cagan$1 (Bs study more directly, or at least more explicitly, than the other studies in this volume. But the work of all contributors to the volume bears quite closely on the problem to which the introduction and Cagan$1 (Bs study are devoted. In these two pieces the concept of the (3z(Bslack(3y (Bavailable for the production of additional output plays a prominent role, and so does the question of what amount of slack may become associated with alternative policies. The now conventional methods of estimating the slack are seriously misleading, and the reasons for this cannot be understood without paying a good deal of attention to the structural problems with which the bulk of this volume is concerned.s
rpm 08/05/2017
Loans
Keywords: Inflation (Finance) $1 (BUnited Statess; Fiscal policy $1 (BUnited States.s; Monetary policy $1 (BUnited States.s; Inflation [Finance] $1 (BUnited States $1 (BAddresses, essays, lectures.s; United States $1 (BEconomic policy $1 (B1971-s; United States $1 (BEconomic conditions $1 (B1971-s; United States $1 (BEconomic policy $1 (B1971- $1 (BAddresses, essays, lectures.s; United States $1 (BEconomic conditions $1 (B1971- $1 (BAddresses, essays, lectures.s; United States $1 (BEconomic policy $1 (B1971-1981.s; United States $1 (BEconomic conditions $1 (B1971-1981.s; United States